IMPLEMENTASI ZMIJEWSKI MODEL DALAM MENILAI KESULITAN KEUANGAN PERUSAHAAN SEKTOR PROPERTI DI BURSA EFEK INDONESIA (Jurnal Ekonomi Bisnis dan Akuntansi, 2021)
This study aims to determine and analyze the calculation of the Zmijewski model in the property industry and predict which companies are in the category of potentially experiencing financial difficulties. The variables used in this study are the Zmijewski X-Score method, financial ratios and bankruptcy score results. The samples used are 6 property companies listed on the Indonesia Stock Exchange from the 2019-2021 period. This study uses the Zmijewski X-Score analysis method which is proxied by the ratio of liquidity, leverage, profitability. The results showed that the Zmijewski model can be used to assess the level of company health, the next result shows that bankruptcy analysis using the Zmijewski method in the property industry shows results, all property companies are declared as healthy companies and free from financial difficulties. The third result shows that the ratio of return on assets, debt ratio and current ratio plays a major role in determining the results of bankruptcy scores in the property industry. Keywords: Financial Distress, ROA, Debt Ratio, Zmijewski Model.